'n Herwaardering van Olga Kirsch se oeuvre: Identiteit ,moederskap en ballingskap aan die hand van die psigoanalitiese toeriee van onder andere Sigmund Freud,Jaques Lacan en Julia Kristeva - Minnaar, William Frank Thomas (School of Languages and Literatures, 2019)
An investigation into the works of poet Olga Kirsch according to psychoanalytical theories reveals interesting possibilities about Afrikaans's sole expressly Jewish poet and only the second female poet to get published in this language. Her yearning to be accepted in Afrikaans circles seems to have been thwarted by the rise of racist Nationalist power. Motherhood, a career as educator and having an allochthonous creative language in Hebrew-speaking Israel were some of the factors that muffled the immigrant Kirsch's poetic voice for more than two decades after arriving in Israel in 1948. An inability to make a breakthrough in Modern Hebrew or English redirected her attention to the language she felt best at home in - Afrikaans. Kirsch, however, could not continue writing poetry indefinitely in a language she had been isolated from for so long. Psychoanalysis explores the drives behind Kirsch's writings: the flight from the phallic mother, loss of the paternal love object, longing for wholeness in the safety of the chora, as well as self-actualisation and jouissance through the creative process. Kirsch is reaffmned as an important Afrikaans poet who, with each volume of poetry, shared her life as a sujet en proces with her Afrikaans-speaking readers. Whereas Sigmund Freud's basic tenets and further developments in psychoanalysis by Jacques Lacan form the underlying structure of this research, extensive insights from the prolific theoretician Julia Kristeva have been employed to counterpoint the masculine and arguably paternalistic views of the former two psychoanalysists. Some rediscovered poems have been included in this thesis and comments by Kirsch's family also add a new dimension to our understanding of her as a person and of her creative output. Further sources of information were found in a documentary about the poet, recordings for radio and articles in newspapers and literary magazines. In order to establish Kirsch's value and durability as an Afrikaans poet, the canonisation process and possible changes to the poet's position in it were also taken into account. It appears from these that Olga Kirsch is, albeit not one of the greatest poets due to her increasingly dated language, nevertheless an indispensable part of the Afrikaans literary canon.